A Novel Based On Image Blocking Method To Encrypt-Decrypt Color - Jamil Al-Azzeh; Bilal Zahran; Ziad Alqadi; Belal Ayyoub; Muhammed Mesleh (Politeknik Negeri Padang, 2019)
Encryption of digital color image is the process of conversion original digital color image into an encrypted one to protect the image from hacking or to prevent an authorized person to get the valuable information located in the color image. The process of color image encryption-decryption is very important issue in human activities and here in this paper we will introduce a new simple, efficient and highly secure method to be used for color image encryption-decryption. The proposed method will be tested and implemented, the efficiency parameters of the proposed method will be calculated and will be compared with other methods parameters to prove the efficiency issues of the proposed method.